Antiviral Activities of Human Host Defense Peptides - Brice, David C.; Diamond, Gill (Current Medicinal Chemistry, 2020)
Peptides with broad-spectrum antimicrobial activity are found widely expressed throughout nature. As they participate in a number of different aspects of innate immunity in mammals, they have been termed Host Defense Peptides (HDPs). Due to their common structural features, including an amphipathic structure and cationic charge, they have been widely shown to interact with and disrupt microbial membranes. Thus, it is not surprising that human HDPs have activity against enveloped viruses as well as bacteria and fungi. However, these peptides also exhibit activity against a wide range of non-enveloped viruses as well, acting at a number of different steps in viral infection. This review focuses on the activity of human host defense peptides, including alpha- and beta-defensins and the sole human cathelicidin, LL-37, against both enveloped and non-enveloped viruses. The broad spectrum of antiviral activity of these peptides, both in vitro and in vivo suggest that they play an important role in the innate antiviral defense against viral infections. Furthermore, the literature suggests that they may be developed into antiviral therapeutic agents.
Keywords: LL-37